(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Anthroponyms – the personal names of individuals – are a rich source of linguistic, cultural, and sociological insight. Drawing on major linguistic theories (structuralism, sociolinguistics, semiotics) and integrating contributions from Uzbek scholars (Sh. Rahmatullaev, O. Qilichev, B. Hasanov, I. Koziyeva, among others), we outline the evolution of naming practices from pre-Islamic times through the Islamic period, Soviet era, post-independence revival, and the contemporary globalization era. A mixed-methods approach was applied: qualitatively, we analyzed the semantic and cultural motivations of personal names, and quantitatively, we surveyed name frequencies and origins across historical periods and gender. In Andijan, an area known for its dense population and deep-rooted traditions, naming patterns illustrate the national trends: for example, the prevalence of Islamic names today alongside the preservation of older naming customs. Gendered naming practices were observed, with male names often conveying strength or religious virtue and female names often embodying beauty or familial hopes.